Career development for infection and immunity research in Uganda: a decade of experience from the Makerere University – Uganda Virus Research Institute research and training programme [version 2; peer review: 2 approved] - Nakanjako, Damalie; Zalwango, Flavia; Wairagala, Pamela; Luboga, Fiona; Andia Biraro, Irene; Bukirwa, Victoria Diana; Mboowa, Mary Gorrethy; Cose, Steve; Seeley, Janet; Elliott, Alison (AAS Open Research, 2020)
The Makerere University/Uganda Virus Research Institute (UVRI) Centre of Excellence for Infection & Immunity Research and Training (MUII) is a collaborative programme supporting excellence in Infection and Immunity (I&I) research in Uganda. Set up in 2008, MUII aims to produce internationally competitive Ugandan and East African I&I research leaders, and develop human and infrastructural resources to support research and training excellence. We undertook an internal evaluation of MUII’s achievements, challenges and lessons learned between 08-2008 and 12-2019, to inform programmes seeking to build Africa’s health research expertise. Methods: Quantitative data were abstracted from programme annual reports. Qualitative data were obtained in 03-04/2019: a crosssectional evaluation was undertaken among a purposefully selected representative sample of 27 trainees and two programme staff. Qualitative data was analysed according to pre-determined themes of achievements, challenges, lessons learned and recommendations for improvement. Results: By 12-2019, MUII had supported 68 fellowships at master’s- level and above (50% female: 23 Masters, 27 PhD, 15 post-doctoral, three group-leaders) and over 1,000 internships. Fellows reported career advancement, mentorship by experts, and improved research skills and outputs. Fellows have published over 300 papers, secured grants worth over £20m, established over 40 international collaborations, and taken on research and academic leadership positions in the country. Key lessons were: i) Efficient administration provides a conducive environment for high quality research; ii) Institutions need supportive policies for procurement, including provisions for purchases of specific biological research reagents from international manufacturers; iii) Strong international and multidisciplinary collaboration provides a critical mass of expertise to mentor researchers in development; and iv) Mentorship catalyses young scientists to progress from graduate trainees to productive academic researchers, relevant to society’s most pressing health challenges. Conclusions: Sustainable academic productivity can be achieved through efficient operational support, global collaboration and mentorship to provide solutions to Africa’s health challenges.
Keywords: Academic careers; Capacity building for research; Infection and Immunity; Immunology; Bioinformatics; Mentorship; Collaboration; Partnership; Sub-Saharan Africa